Investigation of charge-transfer dynamics in organic materials for solar cells - Weisspfennig, CT (2014)
This thesis improves our understanding of the charge-transfer dynamics in organic materials employed in dye-sensitized and nanotube-thiophene solar cells. For the purpose of this work, a femtosecond transient absorption spectroscopy setup was built. Additionally, microsecond transient absorption spectroscopy was utilised to explore dynamics on a longer time-scale. In the first study, the dependence of dye regeneration and charge collection on the pore- filling fraction (PFF) in solid-state dye-sensitized solar cells (DSSCs) is investigated. It is shown that while complete hole transfer with PFFs as low as ~30% can be achieved, improvements beyond this PFF are assigned to a stepwise increase in the charge-collection efficiency in agreement with percolation theory. It is further predicted that the chargecollection efficiency saturates at a PFF of ~82%. The study is followed by an investigation of three novel hole-transporting materials for DSSCs with slightly varying HOMO levels to systematically explore the possibility of reducing the loss-in-potential and thus improving the device efficiency. It is shown that despite one new HTM showing a 100% hole-transfer yield, all devices based on the new HTMs performed worse than those incorporating spiro-OMeTAD. Furthermore, it is demonstrated that the design of the HTM has an additional impact on the electronic density of states present at the TiO2 electrode surface, and hence influences not only hole- but also electron-transfer from the sensitizer. Finally, a study on a polymer-single-walled carbon nanotube (SWNT) molecular junction is presented. Results from femtosecond spectroscopic techniques show that the polymer poly(3-hexylthiophene) (P3HT) is able to transfer charges to the SWNT within 430 fs. Addition of excess P3HT polymer leads to long-lived free charges making these materials a viable option for solar cells.